Pb2+-N bonding chemistry: recycling of polyaniline-pb nanocrystals waste for generating high-performance supercapacitor electrodes - Jha, Plawan Kumar; Singh, Santosh K.; Gatla, Suresh; Mathon, Olivier; Kurungot, Sreekumar; Ballav, Nirmalya (Journal of Physical Chemistry C, 2016)
Understanding of Pb-N bonding chemistry is not only fundamentally important in the view of relativistic inert-pair effect but also is important for therapeutic as well as environmental applications. In the present study, an unusual reactivity of N-containing pi-conjugated polyaniline emeraldine base (EB) toward aqueous Pb2+ ions has been identified. In the course of sequestering Pb2+ ions by EB, cuboid-shaped nanocrystals were isolated. Synchrotron-based X-ray absorption near-edge structure and extended X-ray absorption fine structure techniques were employed to understand Pb-N bonding chemistry in EB-Pb nanocrystals. The adopted methodology of slow exposure of HCl vapor to EB-Pb nanomaterial facilitated the isolation of polyaniline emeraldine-salt (ES) with unique morphological patterns, porosity and electrical conductivity. The electrochemical device based on recycled ES showed high-capacitance value (similar to 606 F/g @1 A/g and similar to 663 F/g @10 mV/s), high-energy density (similar to 14.8 Wh/kg at power density of similar to 663 W/kg) and excellent-cycling stability (only similar to 15% degradation after 1100 continued cycles at current density of 5 A/g). Notably, ES materials prepared directly from EB and upon exposing HNO3 vapor exhibited greatly inferior device performance.

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.